2010
DOI: 10.1111/j.1440-1746.2009.06160.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor‐kappa B as a promising target for selenium chemoprevention in rat hepatocarcinogenesis

Abstract: The inhibition of the NF-kappaB pathway in the initiation phase of hepatocarcinogenesis could be a promising target for selenium chemoprevention. However, further studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Additionally, evidence indicates that supplementing with supranutritional selenium can modulate specific pathological changes via various mechanisms, including GPx and TrxR suppressing NF-κB activation and its inflammatory reactions. [166][167][168][169]. Genetic studies have shown that a single nucleotide polymorphism (SNP) at codon 198 of GPx1 is associated with low bone mineral density and increase in the levels of bone turnover markers [170].…”
Section: Selenoproteins In Bone Metabolismmentioning
confidence: 99%
“…Additionally, evidence indicates that supplementing with supranutritional selenium can modulate specific pathological changes via various mechanisms, including GPx and TrxR suppressing NF-κB activation and its inflammatory reactions. [166][167][168][169]. Genetic studies have shown that a single nucleotide polymorphism (SNP) at codon 198 of GPx1 is associated with low bone mineral density and increase in the levels of bone turnover markers [170].…”
Section: Selenoproteins In Bone Metabolismmentioning
confidence: 99%
“…1 Previous studies have shown that it is sufficient to inhibit the development of certain cancers by daily supplementation of 200 μg selenium. 2 Selenium can also reduce the risk of cardiovascular diseases. 3,4 Some researchers have found that selenium can decrease the activity of brain monoamine oxidase B (MAO-B) in adult rats and slow down the aging process.…”
Section: Introductionmentioning
confidence: 99%